2014
DOI: 10.1161/circinterventions.114.001341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Outcomes of Coronary In-Stent Restenosis Across 3-Stent Generations

Abstract: Background-Clinical presentation of bare metal stent in-stent restenosis (ISR) in patients undergoing target lesion revascularization is well characterized and negatively affects on outcomes, whereas the presentation and outcomes of first-and second-generation drug-eluting stents (DESs) remains under-reported. Methods and Results-The study included 909 patients (1077 ISR lesions) distributed as follows: bare metal stent (n=388), first-generation DES (n=425), and second-generation DES (n=96), categorized into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 25 publications
4
44
2
Order By: Relevance
“…(11) It has also been reported that a shortening of the dual antiplatelet therapy period might be possible for patients who are implanted with second-generation DESs. (12) Our study supports previous data that the arterial healing process is smooth (13) and that stent struts are mainly covered with neointima in both early and late phase ISR when second-generation DESs are used. As a result, stent thrombosis can be expected to be rare in patients with secondgeneration DES implantation.…”
Section: Morphologysupporting
confidence: 89%
“…(11) It has also been reported that a shortening of the dual antiplatelet therapy period might be possible for patients who are implanted with second-generation DESs. (12) Our study supports previous data that the arterial healing process is smooth (13) and that stent struts are mainly covered with neointima in both early and late phase ISR when second-generation DESs are used. As a result, stent thrombosis can be expected to be rare in patients with secondgeneration DES implantation.…”
Section: Morphologysupporting
confidence: 89%
“…1 As stated in our article, neoatherosclerosis, which leads to late neointima formation, is seen across all 3 generations of metallic stents. It is our impression that the neointima of second-generation drug-eluting stents (DES) is less vulnerable and, as a result, associated with fewer events when compared with first-generation DES.…”
mentioning
confidence: 63%
“…A Cox regression analysis was carried out to identify whether types of ISR were associated independently with higher incidence of MACEs. Factors related to MACEs were identified by univariate Cox regression analysis and variables with a P value of less than 0.2 (as used by others [15]) were included in the multivariate model. Variables in the multivariable model included nonfocal-type ISR, the presence of diabetes, length of stents, and bifurcation lesions.…”
Section: Discussionmentioning
confidence: 99%